Ethnobotanical Study for Skin Disease Drug by Society in Pidie District - Rubiah Rubiah; Djufri Djufri; Muhibuddin Muhibuddin (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2015)
This research was aimed to determine the types of plants is utilized by the society in Pidie for skin disease drug. Data collected by Participatory Rural Appraisal (PRA) and purposive sampling. Research object are tuha peut, healer, adolescents: 17-20 years, adults: 21-40 years, and the elderly: 60 years. The data were analyzed descriptively. Parameters measured were the types of medicinal plants, how to use medicinal plants. The result showed 57 species of plant are classified into 37 parts used as drug by the people of Pidie. The conclusion of this research is the species of plant most widely used as drug by the society of Pidie based on famili of Anacardiaceae and Euphorbiaceae.